Integrasi UTAUT dan SCT Untuk Studi Empirik Penerimaan Teknologi CISEA - Yudistira Sira Permana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Mobile application has recently gained a massive popularity in organizations due to its benefits such as flexibility, timely and ubiquity. This study was to empirically investigate factors that influence the intention to use CISEA (Corporate Information System and Enterprise Application). CISEA was developed and utilized to facilitate the company to disseminate information to and collect wide range of data from their employees. This study integrated two theories namely the Unified Theory of Acceptance and Use of Technologists (UTAUT) and Social Cognitive Theory (SCT). By applying a quantitative research, this study surveyed PT. Bukit Asam employees. Further, the Partial Least Square Structural Equation Model (SEM-PLS) was used to analyze the data. The results revealed that Effort Expectancy, Facilitating Condition, and Affect has significant effect to intention to use the CISEA. Also Self Efficacy has a significant effect on Effort Expectancy and Affect On the other hand Performance Expectancy, Social Influence, Self Efficacy and Technology Anxiety have no significant effect on intention to use CISEA The research model has provide an effective guideline to evaluate the use of technology CISEA.